Microeconomics of technology adoption - Andrew D. Foster; Mark R. Rosenzweig (Yale University, Economic Growth Center, 2010)
There is an emerging consensus among macro-economists that differences in technology across countries account for the major differences in per-capita GDP and the wages of workers with similar skills across countries. Accounting for differences in technology levels across countries thus can go a long way towards understanding global inequality. One mechanism by which poorer countries can catch up with richer countries is through technological diffusion, the adoption by low-income countries of the advanced technologies produced in high-income countries. In this survey, we examine recent micro studies that focus on understanding the adoption process. If technological diffusion is a major channel by which poor countries can develop, it must be the case that technology adoption is incomplete or the inputs associated with the technologies are under-utilized in poor, or slow-growing economies. Thus, obtaining a better understanding of the constraints on adoption is useful in understanding a major component of growth.
Keywords: O10; O13; O33; 330; technology adoption review; Mikroökonomik; Technologietransfer; Lernprozess; Entwicklungsländer